Islamic-Based Multicultural Education and Its Development Strategies - Wildan Mahmudin; Yanto Maulana Restu; Miswan Ramdani; Slamet; Uus Ruswandi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The increasing number of conflicts due to differences in cultural backgrounds necessitates the search for specific strategies to resolve these issues through various fields: social, political, cultural, economic, and educational. In this regard, multicultural education offers an alternative through the application of educational strategies and concepts based on the utilization of diversity in society, particularly in students such as ethnicity, culture, language, religion, social status, gender, ability, age, and race. In this study, the author uses library research, a series of activities related to library data collection methods. The results of this study indicate that the implementation of multicultural education can be carried out using the following strategies: curriculum development, improving the professional quality of educational staff, developing an educational management system, developing a higher education system, harmonizing public perceptions, instilling recognition (understanding) and appreciation for diversity (culture, ethnicity, race, religion, outlook on life, and so on), avoiding views that assume that one group is superior to another, and fostering and habituating a deliberative attitude.